2014
DOI: 10.1177/1359105314523304
|View full text |Cite
|
Sign up to set email alerts
|

‘Making every contact count’: Evaluation of the impact of an intervention to train health and social care practitioners in skills to support health behaviour change

Abstract: A total of 148 health and social care practitioners were trained in skills to support behaviour change: creating opportunities to discuss health behaviours, using open discovery questions, listening, reflecting and goal-setting. At three time points post-training, use of the skills was evaluated and compared with use of skills by untrained practitioners. Trained practitioners demonstrated significantly greater use of these client-centred skills to support behaviour change compared to their untrained peers up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 26 publications
(31 reference statements)
5
118
0
Order By: Relevance
“…Such targeting could involve training line managers in basic communication methods to encourage people to engage with health services (Lawrence et al . ). Recruitment could also be enhanced by targeting the Line Mangers' sense of responsibility using specific marketing tools that highlight the importance of helping their staff maintain good health, for example by encouraging them to attend a workplace LIP ( e.g .…”
Section: Discussionmentioning
confidence: 97%
“…Such targeting could involve training line managers in basic communication methods to encourage people to engage with health services (Lawrence et al . ). Recruitment could also be enhanced by targeting the Line Mangers' sense of responsibility using specific marketing tools that highlight the importance of helping their staff maintain good health, for example by encouraging them to attend a workplace LIP ( e.g .…”
Section: Discussionmentioning
confidence: 97%
“…As a result of the training, staff changed the way they interacted with women, using open discovery questions, listening more than talking and empowering women to set goals. These changes were still apparent one year after training [56]. Evaluation showed that women who came into contact with trained staff had significantly smaller declines in their sense of control and self-efficacy than women in the control group, although an effect on diet was not observed [57].…”
Section: Interventionsmentioning
confidence: 99%
“…After training, staff demonstrated sustained changes to the way they worked with women attending SSCCs, and were more confident in supporting lifestyle changes [29]. Changes to the way staff worked were still evident a year post-training [30]. A non-randomised controlled trial of the effect of exposure to trained staff on diet and physical activity levels in women attending SSCCs showed that the intervention had no measurable effect on women’s diet and physical activity levels, but that it may have protected against a decline in their self-efficacy and perceptions of control over life, factors known to be associated with change in both these health behaviours [31].…”
Section: The Southampton Initiative For Healthmentioning
confidence: 99%